Kekuatan Pembuktian Audit BPK dengan BPKP dalam Perkara Tindak Pidana Korupsi (Studi Putusan Nomor:24/Pid.Sus-TPK/2024/PN Mtr) - Adhar; Abdul Rahman Salman Paris; Safran (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
In corruption cases with the same object and subject audited by different state institutions, the results are different, which creates legal uncertainty. However, the reference for the legal considerations of the panel of judges in the Corruption Crime Court Decision at the Mataram District Court Decision Number: 24 / Pid.Sus-TPK / 2024 / PN Mtr is the BPKP audit results, even though one of the three panels of judges has a different opinion. The results of the study. The evidentiary strength of the BPKP audit results with the BPK when the two state institutions, namely the BPK and BPKP, calculate state losses in the same case (item and object). However, there are differences and differences, so in terms of evidentiary strength, the BPK audit results must be prioritized because they are of a higher position based on the Constitution and Law and have the authority to audit and declare state financial losses, while the BPKP is based on a Presidential Regulation and does not have the authority to declare state financial losses. Therefore, Decision Number: 24/Pid.Sus-TPK/2024/PN Mtr should disregard the BPKP audit evidence and use the audit by the NTB Provincial Representative Office of the BPK.